Organic carbon deposition and phosphorus accumulation during Oceanic Anoxic Event 2 in Tarfaya, Morocco - Mort, Haydon P.; Adatte, Thierry; Keller, Gerta; Bartels, David; Föllmi, Karl B.; Steinmann, Philipp; Berner, Zsolt; Chellai, E.H. (My University, 2008)
With a multi-proxy approach, an attempt was made to constrain productivity and bottom-water redox conditions and their effects on the phosphorus accumulation rate at the Mohammed Plage section on the Tarfaya coast, Morocco, during the Cenomanian-Turonian Anoxic Event (OAE 2). A distinct δ13Corg isotope excursion of +2.5‰ occurs close to the top of the section. The unusually abrupt shift of the isotope excursion and disappearance of several planktonic foraminiferal species (e.g. Rotalipora cushmani and Rotalipora greenhornensis) in this level suggests a hiatus of between 40–60 kyrs at the excursion onset. Nevertheless, it was possible to determine both the long-term environmental history as well as the processes that took place immediately prior to and during OAE 2. TOC% values increase gradually from the base of the section to the top (from ~ 2.5% to ~ 10%). This is interpreted as the consequence of a long-term eustatic sea-level rise and subsidence causing the encroachment of less oxic waters into the Tarfaya Basin. Similarly a reduction in the mineralogically constructed ‘detrital index’ can be explained by the decrease in the continental flux of terrigenous material due to a relative sea-level rise. A speciation of phosphorus in the upper part of the section, which spans the start and mid-stages of OAE 2, shows overall higher abundances of Preactive mass accumulation rates before the isotope excursion onset and lower values during the plateau. Due to the probable short hiatus, the onset of the decrease in phosphorus content relative to the isotope excursion is uncertain, although the excursion plateau already contains lower concentrations. The Corg/Ptotal and V/Al ratios suggest that this reduction was mostly likely caused by a decrease in the available bottom oxygen content (probably as a result of higher productivity) and a corresponding fall in the phosphorus retention ability of the sediment. Productivity appears to have remained high during the isotope plateau possibly due to a combination of ocean-surface fertilisation via increased aridity (increased K/Al and Ti/Al ratios) and/or higher dissolved inorganic phosphorus content in the water column as a result of the decrease in sediment P retention. The evidence for decreased P-burial has been observed in many other palaeoenvironments during OAE 2. Tarfaya's unique upwelling paleosituation provides strong evidence that the nutrient recycling was a global phenomenon and therefore a critical factor in starting and sustaining OAE 2.
Keywords: Anoxia; Phosphorus burial; Organic carbon; Morocco; Cenomanian-Turonian